Left Module over Ring Induces Right Module over Opposite Ring

From ProofWiki
Jump to navigation Jump to search


Let $\struct {R, +_R, \times_R}$ be a ring.

Let $\struct {R, +_R, *_R}$ be the opposite ring of $\struct {R, +_R, \times_R}$.

Let $\struct{G, +_G, \circ}$ be a left module over $\struct {R, +_R, \times_R}$.

Let $\circ’ : G \times R \to G$ be the binary operation defined by:

$\forall \lambda \in R: \forall x \in G: x \circ’ \lambda = \lambda \circ x$

Then $\struct{G, +_G, \circ’}$ is a right module over $\struct {R, +_R, *_R}$.


It is shown that $\struct{G, +_G, \circ’}$ satisfies the right module axioms

By definition of the opposite ring:

$\forall x, y \in R: x *_R y = y \times_R x$.

$(RM \, 1)$ : Scalar Multiplication (Right) Distributes over Module Addition

Let $\lambda \in R$ and $x, y \in G$.

\(\displaystyle \paren{x +_G y} \circ’ \lambda\) \(=\) \(\displaystyle \lambda \circ \paren{x +_G y}\) Definition of $\circ’$
\(\displaystyle \) \(=\) \(\displaystyle \lambda \circ x +_G \lambda \circ y\) Left module axiom $(M \, 1)$ on $\struct{G, +_G, \circ}$
\(\displaystyle \) \(=\) \(\displaystyle x \circ’ \lambda +_G y \circ’ \lambda\) Definition of $\circ’$


$(RM \, 2)$ : Scalar Multiplication (Left) Distributes over Scalar Addition

Let $\lambda, \mu \in R$ and $x \in G$.

\(\displaystyle x \circ’ \paren {\lambda +_S \mu}\) \(=\) \(\displaystyle \paren {\lambda +_R \mu} \circ x\) Definition of $\circ’$
\(\displaystyle \) \(=\) \(\displaystyle \lambda \circ x +_G \mu \circ x\) Left module axiom $(M \, 2)$ on $\struct{G, +_G, \circ}$
\(\displaystyle \) \(=\) \(\displaystyle x \circ’ \lambda +_G x \circ’ \mu\) Definition of $\circ’$


$(RM \, 3)$ : Associativity of Scalar Multiplication

Let $\lambda, \mu \in S$ and $x \in G$.

\(\displaystyle x \circ’ \paren {\lambda *_R \mu}\) \(=\) \(\displaystyle \paren {\lambda *_R \mu} \circ x\) Definition of $\circ’$
\(\displaystyle \) \(=\) \(\displaystyle \paren {\mu \times_R \lambda} \circ x\) Definition of $*_R$
\(\displaystyle \) \(=\) \(\displaystyle \mu \circ \paren {\lambda \circ x}\) Left module axiom $(M \, 3)$ on $\struct{G, +_G, \circ}$
\(\displaystyle \) \(=\) \(\displaystyle \mu \circ \paren{x \circ’ \lambda}\) Definition of $\circ’$
\(\displaystyle \) \(=\) \(\displaystyle \paren{x \circ’ \lambda} \circ’ \mu\) Definition of $\circ’$


Also see